2018
DOI: 10.31289/jkbm.v5i1.1875
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Produk Domestik Bruto, Infrastruktur, Nilai Tukar Dan Tingkat Suku Bunga Terhadap Investasi Asing Langsung Di Indonesia

Abstract: <p>Penelitian ini bertujuan untuk memberikan bukti empiris tentang faktor-faktor yang mempengaruhi investasi asing langsung di Indonesia dalam perkembangan ekonomi global yang meliputi produk domestik bruto, infrastruktur, nilai tukar dan suku bunga untuk periode 1998 - 2015. Metode analisis yang digunakan adalah persamaan regresi linier berganda. dengan teknik analisis Ordinary Least Square (OLS) dan Error Correction Mechanism (ECM). Hasil empiris dari penelitian menunjukkan bahwa dalam jangka panjang v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
1
0
1
Order By: Relevance
“…With more value, they are more likely to be able to obtain more products or services than when the exchange rate depreciates. Therefore, this result is in accordance with researches conducted by Batubara et al (2022), Astuty and Siregar (2018), Polyxeni andTheodore (2019), andRazak et al (2018), where foreign direct investment is affected significantly by exchange rate, and H3 is accepted in this study.…”
Section: Results and Discusssionsupporting
confidence: 89%
See 1 more Smart Citation
“…With more value, they are more likely to be able to obtain more products or services than when the exchange rate depreciates. Therefore, this result is in accordance with researches conducted by Batubara et al (2022), Astuty and Siregar (2018), Polyxeni andTheodore (2019), andRazak et al (2018), where foreign direct investment is affected significantly by exchange rate, and H3 is accepted in this study.…”
Section: Results and Discusssionsupporting
confidence: 89%
“…In addition, the trend of interest rates from year to year shows a constant number, in contrast to foreign direct investment which has significant changes. Therefore, this result is supported by research done by Chandra and Handoyo (2020), Latief and Lefen (2018), Astuty and Siregar (2018), and Sasana and Fathoni (2019). In their research, they found that foreign direct investment does not affected significantly by interest rate.…”
Section: Results and Discusssionsupporting
confidence: 69%
“…Pengaruh PDB Terhadap Investasi FDI Di Indonesia Dari hasil regresi diketahui bahwa PDB memberikan dampak positif namun tidak signifikan terhadap investasi FDI di Indonesia. Dengan melihat nilai koefisien regresi parsial (β1) sebesar 0,731 hal ini menunjukan bahwa setiap kenaikan 1 tahun PDB searah dengan meningkatnya investasi FDI sebesar 0,731% namun kenaikan PDB tidak mempengaruhi kenaikan pada investasi FDI ditunjukkan oleh nilai probalitas (0.647) Hasil ini sama dengan penelitian terdahulu (Agung dkk., 2018) namun berbeda pada signifikan variabelnya dengan penelitian (Astuti & Siregar, 2018) menunjukan bahwa pertumbuhan ekonomi berpengaruh positif terhadap investasi FDI di Indonesia. PDB merupakan indicator pertumbuhan ekonomi yang mempunyai dampak positif terhadap investasi FDI, dikarenakan PDB yang meningkat akan menarik investor untuk berinvestasi (Sarwedi, 2002).…”
Section: Uji Signifikansi Parsial (Uji Statistik T)unclassified
“…This statement is supported by Amirsyah, (2020) who examines the determinants of foreign direct investment in ASEAN, Japan, South Korea, and China finding that GDP and exports have a significant positive effect on foreign direct investment. Astuty & Siregar, (2018); Hoang Quoc Chi Duong Thi, (2018) also strengthen by analyzing the effect of GDP in Indonesia and Vietnam on FDI having a positive impact. In addition, Baskara & Sulasmiyati, (2017) have the same view that GDP can have a positive influence on FDI in Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%